Biofortified yellow cassava and vitamin A status of Kenyan children: a randomized controlled trial. Issue 1 (16th December 2015) - Talsma, Elise F; Brouwer, Inge D; Verhoef, Hans; Mbera, Gloria NK; Mwangi, Alice M; Demir, Ayşe Y; Maziya-Dixon, Busie; Boy, Erick; Zimmermann, Michael B; Melse-Boonstra, Alida
ABSTRACT: Background: Whereas conventional white cassava roots are devoid of provitamin A, biofortified yellow varieties are naturally rich in β-carotene, the primary provitamin A carotenoid. Objective: We assessed the effect of consuming yellow cassava on serum retinol concentration in Kenyan schoolchildren with marginal vitamin A status. Design: We randomly allocated 342 children aged 5–13 y to receive daily, 6 d/wk, for 18.5 wk 1 ) white cassava and placebo supplement (control group), 2 ) provitamin A–rich cassava (mean content: 1460 μg β-carotene/d) and placebo supplement (yellow cassava group), and 3 ) white cassava and β-carotene supplement (1053 μg/d; β-carotene supplement group). The primary outcome was serum retinol concentration; prespecified secondary outcomes were hemoglobin concentration and serum concentrations of β-carotene, retinol-binding protein, and prealbumin. Groups were compared by using ANCOVA, adjusting for inflammation, baseline serum concentrations of retinol and β-carotene, and stratified design. Results: The baseline prevalence of serum retinol concentration <0.7 μmol/L and inflammation was 27% and 24%, respectively. For children in the control, yellow cassava, and β-carotene supplement groups, the mean daily intake of cassava was 378, 371, and 378 g, respectively, and the total daily supply of provitamin A and vitamin A from diet and supplements was equivalent to 22, 220, and 175 μg retinol, respectively. Both yellow cassava and β-carotene supplementation increased serum retinol concentration by 0.04 μmol/L (95% CI: 0.00, 0.07 μmol/L); correspondingly, serum β-carotene concentration increased by 524% (448%, 608%) and 166% (134%, 202%). We found no effect on hemoglobin concentration or serum concentrations of retinol-binding protein and prealbumin. Conclusions: In our study population, consumption of yellow cassava led to modest gains in serum retinol concentration and a large increase in β-carotene concentration. It can be an efficacious, new approach to improve vitamin A status. This study was registered with clinicaltrials.gov as NCT01614483.